Squamous Cell Carcinoma of External Auditory Canal with Intracranial Infiltration - Damayanthi, M. Ayu Dwi; Nuaba, I Gde Ardika; Suanda, I Ketut; Widiantari, Ida Ayu Alit (CV. Publikasi Indonesia, 2025)
Squamous cell carcinoma of external auditory canal (SCC EAC) is a rare malignancy with the incidence of <0.2% of all malignancies of the head and neck region. This disease often mimics the features of other diseases as in chronic suppurative otitis media of the dangerous type with cholesteatoma. SCC EAC the most common malignancy pathology, reaching 90% of malignancies in the temporal bone and external auditory canal. This case report describes a patient with SCC in EAC with infiltration to intracranial. A 42 years old man with a history of discharge and blood from his left ear. Based on the history, clinical presentation and Computed Tomography (CT) Scan of the mastoid, found there was a mass in the left ear with intracranial infiltration. The results of histopathological examination obtained SCC EAC stage IV (T4N2M0) + infiltration of the cerebellum region S + non-communicating hydrocephalus. The patient already done a surgery. This case represents a rare presentation of SCC EAC with intracranial involvement in a relatively young patient (42 years), which is uncommon as most cases occur in patients aged 60-69 years. The aggressive nature with cerebellar infiltration and non-communicating hydrocephalus demonstrates the importance of early detection and multidisciplinary management. This case contributes to the limited literature on advanced SCC EAC with CNS involvement and emphasizes the need for comprehensive staging and aggressive surgical intervention.